Customers’ Purchase Intentions on Herbal Products and Supplements During the COVID-19 Pandemic - Syafrizal Syafrizal; Idris Gautama So; Ali Vafaei-Zadeh (Bina Nusantara University, 2024)
The research aimed to extend the Theory of Planned Behavior (TPB) by including health consciousness and health value as predictors of purchase intention on herbal products and supplements. The research applied quantitative hypothesis testing. Then, the convenience sampling technique was used in collecting research data. The survey was conducted on 260 herbal and supplement customers in West Sumatra. The research instrument was adapted from previous studies. Then, the research data were analyzed using Structural Equation Modelling (SEM) techniques with the software SmartPLS 3.0. The testing of extended TPB in the research finds that health consciousness and health value have a positive and significant effect on customers’ attitudes and purchase intentions. Among the three main predictors of purchase intention in TPB (customer attitude, subjective norm, and behavioral control), only control behavior positively and significantly affects purchase intention. This extended TPB contributes to the theory of purchase intention by including health consciousness and health value as new predictors in customers’ purchase intentions, especially for herbal products and supplements. The research implications are that marketers and other stakeholders need to carry out effective marketing communications about products and events that support the development of healthy patterns and lifestyles and spend some effort to facilitate consumers' access to herbal products and supplements.